Graduates’ Perspective & Assessment of Program Learning Outcome (PLO) of Electrical Engineering Department Based on Exit Survey at Sultan Idris Shah Polytechnic (PSIS) - Paisan, Mohd Farhan’Uzair; Che Kadir, Budiah Karmilie; Nor Shah, Nor Ima (Research and Innovation in Technical and Vocational Education and Training, 2023)
The purpose of the graduate survey is to obtain opinions and impressions of program learning outcome from students rather than being evaluated by faculty. This survey is also useful to assess the quality of education in the Department of Electrical Engineering (JKE) of Sultan Idris Shah Polytechnic (PSIS) and to identify elements for improving the electrical engineering programs. A sample of 181 respondents, who completed the study in session 1 2021/2022 and December 2020 is gathered. A set of questionnaires is developed to assess the achievement of the Electrical Engineering Department program learning outcome (PLOs) from the graduate perspective and to obtain perception of the facilities and resources provided. Google form is used as the platform to collect the responses. The survey consists of three sections: demographic data, 12 program learning outcome (PLOs) achievement from the graduate perspective, and students perceptions of the facilities and resources provided. Descriptive analysis being used to analyze the data collected. Results show that all 12 PLOs were successfully achieved upon graduation, with high and very high score. The results of this survey can be compared to the results of the faculty (through formal assessment by the department). The findings also show that the majority of the respondents are satisfied with the facilities and resources offered Department of Electrical Engineering (JKE) of Sultan Idris Shah Polytechnic (PSIS). However, the survey suggests that graduate favour if the education provider offers a more stable internet connection on the campus.